2010
DOI: 10.1007/s11897-010-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

Depression After Myocardial Infarction

Abstract: Depression is an important disease state that requires significant time and resources to manage properly. The presence of depression in patients with cardiovascular disease has been strongly associated with detrimental effects in terms of morbidity and mortality. Although several large-scale and small studies have evaluated various interventions in the management of depression after myocardial infarction, a significant portion of these data have provided more questions than answers. Although limited, the rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
1
6
0
1
Order By: Relevance
“…We did not detect a significant increase in the presence of substantial depressive symptoms after MI hospitalization 38 when controlling for depressive symptoms prior to the acute event, similar to previous MI research. 15 Still, we observed that having a higher number of functional impairments after acute MI or stroke was independently associated with substantial depressive symptoms, consistent with studies of other acute medical events like pneumonia and sepsis.…”
Section: Discussionsupporting
confidence: 89%
“…We did not detect a significant increase in the presence of substantial depressive symptoms after MI hospitalization 38 when controlling for depressive symptoms prior to the acute event, similar to previous MI research. 15 Still, we observed that having a higher number of functional impairments after acute MI or stroke was independently associated with substantial depressive symptoms, consistent with studies of other acute medical events like pneumonia and sepsis.…”
Section: Discussionsupporting
confidence: 89%
“…Peripheral vascular disease is often paired with comorbid cerebrovascular disease [38], and is a determinant of worse outcomes in patients with myocardial infarction [39]. There also is a link between both cerebrovascular disease [40] and myocardial infarction [41] and depression. Thus, end-organ damage of global vascular disease appeared to be central to this profile.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the barriers and facilitators to accessing preventive and rehabilitative healthcare services can help reduce the risks of adverse outcomes for cardiac conditions and common comorbidities. In particular, depression and other mood and anxiety disorders are increasingly recognized as a complication of AMI [4][5][6], which can lead to increased risk of mortality [7][8][9]. Some research suggests that women may demonstrate a higher risk of anxiety or depression following an AMI compared to men [10].…”
Section: Introductionmentioning
confidence: 99%